DISTANCE LEARNING USING NEWS ITEMS-ANDROID APPLICATION TO IMPROVE STUDENTS' ENGLISH COMPETENCE INTEGRATED WITH COVID-19 PREVENTION - Didit Kurniadi; Suprapto Suprapto (PHILOSOPHICA Jurnal Bahasa, Sastra, dan Budaya, 2021)
Covid-19 is not over yet while the learning process in schools must continue for the sake of great future generations. There are many problems or obstacles in implementing distance learning to avoid Covid-19. This study aims to produce a product design in the form of media or teaching materials that can be used in the distance learning as a form of improving English competence and socializing Covid-19. The method used in this research is the research & development (R&D) method. The research was carried out in several stages such as preliminary, prototyping, expert validation, product trials taken from several samples, in order to design/application products that are ready to be used to help teachers and students in the distance learning. The design and materials of teaching materials are adjusted to the results of data collection at the preliminary stage. This android application was tested on students and teachers with satisfactory results above 70% because it is easy to use based on the results of the distributed questionnaire. The materials and exercises already represent the learning objectives in the curriculum regarding news items. The Covid-19 socialization integrated in the learning application is used as additional information for students to carry out strict health protocols. So that students know what actions need to be taken in their family, friendship, and social life to avoid Covid-19.